Setting boundaries on the definition of "Practice of Law" in Philippine Jurisprudence notes (2020)
A video in which a lawyer explains legal concepts in an episode of a television show' and a video lecture on law in an online learning platform— both of these were formulated for informational purposes, and yet both fall under the Philippine definition of "practice of law."

The Supreme Court, in a line of decisions traceable to the landmark case of Cayetano v. Monsod, defines the practice of law as "any activity, in or out of court, which requires the application of law, legal procedure, knowledge, training, and experience. It includes performing acts which are characteristic of the legal profession, or rendering any kind of service which requires the use in any degree of legal knowledge or skill."

Curiously, the Court did not settle for a single definition of the term "practice of law" in its decision in Cayetano but merely cited a number of definitions from various sources. Proposing a single definition combining all of the above sources, however, is not the goal of this paper.
Keywords: Practice of law; Definitions